Evidence that vitamin D3 reverses age-related inflammatory changes in the rat hippocampus. (1st August 2005) - Moore, M.E.; Piazza, A.; McCartney, Y.; Lynch, M.A.
Abstract : One of the major challenges in neuroscience is to identify the changes which accompany aging and which contribute to the well-documented age-related deterioration in cognitive function. This is a particular challenge in the light of the vast array of reported changes, which include morphological changes like synaptic and perhaps cell loss, alteration in membrane composition and the resultant changes in function of membrane proteins, modulation of the hypothalamo–pituitary axis, impaired calcium homoeostatic mechanisms, alteration in enzyme function and decreased neurotransmitter release. In the past few years, evidence suggesting that an aged brain exhibits signs of oxidative stress and inflammatory stress has been accumulating, and recent evidence using microarray analysis has added support to this view. In this paper, we provide evidence to suggest that vitamin D3 acts as an anti-inflammatory agent and reverses the age-related increase in microglial activation and the accompanying increase in IL-1β (interleukin-1β) concentration.